2007
DOI: 10.22495/cocv4i2c1p6
|View full text |Cite
|
Sign up to set email alerts
|

Corporate governance and firm performance in an emerging market - An exploratory analysis of Pakistan

Abstract: This preliminary study aims to develop a corporate governance index based on governance practices followed by the listed firms at Karachi Stock Exchange (KSE). Since the corporate governance concept is at very initial level of its implementation and practices, this study also analyses the structure of good corporate governance practices and level of awareness about new regulations of corporate governance implemented by Security Exchange Commission of Pakistan. The data is collected through a structured questio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 32 publications
0
4
0
Order By: Relevance
“…The sample size of the present study is analogous to the earlier studies such as Udin et al (2017), Akbar et al (2016), Manzaneque et al (2016), Shahwan (2015), Wahba (2015), Kamel and Shahwan (2014), Tariq and Abbas (2013), Javid and Iqbal (2010), Javed and Iqbal (2007), and Shaheen and Nishat (2005). The listed non-financial companies showed a growth of 13.57% in size and 9.26% in shareholders' equity during the year 2018.…”
Section: Methodsmentioning
confidence: 51%
“…The sample size of the present study is analogous to the earlier studies such as Udin et al (2017), Akbar et al (2016), Manzaneque et al (2016), Shahwan (2015), Wahba (2015), Kamel and Shahwan (2014), Tariq and Abbas (2013), Javid and Iqbal (2010), Javed and Iqbal (2007), and Shaheen and Nishat (2005). The listed non-financial companies showed a growth of 13.57% in size and 9.26% in shareholders' equity during the year 2018.…”
Section: Methodsmentioning
confidence: 51%
“…The main objective of corporate governance in Pakistan is to raising fund from the external capital market. (Nishat & Shaheen, 2007) study the rating of corporate governance base on annual report they find proof that good governance will lead to raise the value of firm. (Javid & Iqbal, 2010) use panel data and concluded that there is positive relationship among the firm level of corporate governance and performance.…”
Section: Corporate Governance In Pakistanmentioning
confidence: 99%
“…Akmal (2007) studied a long-haul association between equity returns and the rate of inflation; he has also concluded that the rate of inflation provided a hedging to the stock returns in a long-term relationship. Nishat and Shaheen (2005) examined a long-haul affiliation between equity returns of the KSE 100 index and economic indicators: for instance, manufacturing productivity, economic growth, and rate of inflation. They covered annual data from 1973 to 2004 and employed a vector error correction model, a variance decomposition method, and a multivariate cointegration econometrics model to examine the series.…”
Section: Literature: the Kse 100 Indexmentioning
confidence: 99%